Coal gangue lightweight aggregate self-curing lightweight concrete and preparation method thereof

By compositely crosslinking sodium hyaluronate and polyvinyl alcohol on coal gangue ceratops and coal gangue ceratops, the shortcomings of lightweight concrete in volume stability and curing are solved, and the lightweight and high-performance self-curing effect of concrete is achieved. .

CN119430774APending Publication Date: 2025-02-14ANHUI DONGCHEN NEW MATERIAL TECH CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411821940.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing lightweight concrete has shortcomings in volume stability and maintenance, making it difficult to meet the needs of modern buildings for lightweight and high-performance materials.

Method used

Coal gangue ceratops and coal gangue ceratops are used as light aggregates, and sodium hyaluronate and polyvinyl alcohol are compositely crosslinked on them. The self-curing capacity and mechanical strength of the concrete are improved through the combination of these materials.

Benefits of technology

The concrete is lightweight and its self-weight is reduced by 20% to 30%. At the same time, the compressive strength, permeability and water bail capacity of the concrete are improved, and its self-conservation effect is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005183306360000101
    Figure BDA0005183306360000101
Patent Text Reader

Abstract

The invention discloses coal gangue lightweight aggregate self-curing lightweight concrete and a preparation method thereof, and belongs to the technical field of concrete.The lightweight concrete is prepared from, by mass, 20%-25% of cement, 0-5% of mineral powder, 5%-10% of fly ash, 25%-40% of coal gangue pottery sand, 20%-40% of coal gangue ceramsite, 0.5%-2% of a water reducing agent and 10%-20% of water; the coal gangue ceramsite is compounded with cross-linked sodium hyaluronate. The coal gangue ceramsite is combined with the coal gangue pottery sand, so that the weight of the concrete can be greatly reduced, the coal gangue ceramsite composite cross-linked sodium hyaluronate with a loose and porous structure has excellent water absorption, and the water retaining and releasing capability of the coal gangue ceramsite composite cross-linked sodium hyaluronate can help to release water outwards when the internal humidity of the concrete is reduced, so that a self-curing effect is realized. And the coal gangue ceramsite compounded with the cross-linked sodium hyaluronate is firmly combined with the cementing material, so that the compressive strength is improved, and the light high-strength self-curing concrete material is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete, and particularly relates to a self-curing lightweight concrete made of coal gangue lightweight aggregate and a preparation method thereof. Background Art

[0002] As a traditional building material, concrete has the advantages of abundant raw materials, low cost, excellent durability and mechanical properties, and is widely used in construction projects, road projects, and bridge projects. Lightweight aggregate plays the role of skeleton and filler in concrete, and is an important component of concrete. Aggregates used in conventional concrete are mostly natural stones, which not only pollute the environment when mined, but are also non-renewable resources. Moreover, when used as concrete skeleton materials, they cannot meet the current development requirements of lightweight concrete.

[0003] Therefore, more and more people are paying attention to the research of high-performance lightweight concrete. Although the use of some porous lightweight aggregates can reduce the deadweight of concrete, it will also lead to a decrease in the volume stability of concrete, weakening the ability of aggregates to limit the shrinkage and deformation of cement stone, thereby increasing the shrinkage and deformation of lightweight concrete. The usual maintenance method is also difficult to penetrate deep into the interior, making it inconvenient to maintain the interior and top surface of the concrete and special component shapes. Summary of the invention

[0004] The object of the present invention is to provide a self-curing lightweight concrete made of coal gangue lightweight aggregate and a preparation method thereof, so as to solve the problems of lightweighting and curing of concrete.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] In the first aspect, the present invention provides a self-curing lightweight concrete made of coal gangue lightweight aggregate, comprising the following raw materials in mass fractions: 20% to 25% cement, 0% to 5% mineral powder, 5% to 10% fly ash, 25% to 40% coal gangue ceramsite, 20% to 40% coal gangue expanded clay, 0.5% to 2% water reducing agent, and 10% to 20% water; the coal gangue expanded clay is compounded with cross-linked sodium hyaluronate.

[0007] Preferably, the gangue ceramsite is cylindrical gangue ceramsite; the particle size of the gangue ceramsite is 12 mm to 14 mm.

[0008] Preferably, the particle size of the coal gangue ceramic sand is 0.2 mm to 1.5 mm.

[0009] Preferably, the water reducer is a polycarboxylate water reducer.

[0010] By adopting the above technical solution, in order to obtain light and high-strength concrete, the present invention uses coal gangue ceramsite combined with coal gangue ceramsite sand to greatly reduce the weight of concrete. The cylindrical coal gangue ceramsite is more convenient for construction and can reduce construction pressure. In addition, the internal structure of coal gangue ceramsite is loose and porous, and its pores are mostly connected. It can release moisture to the outside when the humidity inside the concrete decreases, promote the hydration process of cement, and thus achieve the effect of self-curing.

[0011] However, when gangue ceramsite is used as light aggregate, although it can realize self-curing of concrete materials by utilizing its own water absorption, its water absorption will also cause the working performance, impermeability and antifreeze property of concrete to decrease. For this reason, the gangue ceramsite provided by the present invention is also compounded with cross-linked sodium hyaluronate.

[0012] Cross-linked sodium hyaluronate has a large number of hydrophilic groups and a three-dimensional cross-linked network structure. Compared with coal gangue expanded clay, it can better store liquid water in the polymer network structure. It has the characteristics of fast water absorption and high water absorption rate. It can reduce the water absorption of coal gangue expanded clay itself, thereby improving the working performance and impermeability of concrete. It can also improve the ability of coal gangue expanded clay to release water and enhance the self-curing effect of concrete.

[0013] Preferably, the raw materials of the gangue ceramsite composite cross-linked sodium hyaluronate include gangue ceramsite, sodium hyaluronate and a cross-linking agent in a mass ratio of 1: (0.08-1): (0.06-0.08).

[0014] Preferably, the cross-linking agent includes one or more combinations of 1,4-butanediol diglycidyl ether, glutaraldehyde, polyethylene glycol diglycidyl ether and carbodiimide.

[0015] By adopting the above technical scheme, the present invention connects the molecular chains of sodium hyaluronate to each other to form a cross-linked network structure through the action of a cross-linking agent, which can greatly improve the water retention capacity of sodium hyaluronate, so that when the humidity inside the concrete decreases, it can slowly release moisture to the outside, enhance the density between the coal gangue ceramsite and the concrete cementitious material, and reduce the occurrence of shrinkage deformation of the concrete material.

[0016] At the same time, the cementitious material in the concrete can be embedded in the dense voids of the gangue expanded clay, thereby improving the bonding force between the lightweight aggregate skeleton and the cement. The cross-linked sodium hyaluronate composited with the gangue expanded clay uses its large number of polar groups and cross-linked structures to help form a stronger bond with the concrete cementitious material, thereby improving the mechanical strength of the resulting lightweight concrete and obtaining a lightweight, high-strength, self-curing concrete material.

[0017] Preferably, the coal gangue ceramsite is also compounded with polyvinyl alcohol.

[0018] Preferably, the mass ratio of coal gangue ceramsite to polyvinyl alcohol is 1:(0.03-0.05).

[0019] By adopting the above technical scheme, the composite cross-linked sodium hyaluronate of coal gangue expanded clay can bring a certain self-curing effect to the concrete. However, due to the low mechanical strength of the cross-linked sodium hyaluronate itself, the strength decreases and the volume expands after absorbing a large amount of water. The coal gangue expanded clay is difficult to support, which easily leads to a decrease in the mechanical strength of the obtained coal gangue expanded clay itself. The durability of the lightweight aggregate will decrease, which will reduce the service life of the concrete.

[0020] Therefore, the gangue ceramsite of the present invention is also compounded with polyvinyl alcohol, which also has certain water absorption and water retention properties, and can help disperse the amount of water stored in the cross-linked sodium hyaluronate, while improving the water retention capacity of the gangue ceramsite, without causing the problem of a significant decrease in the mechanical strength of the cross-linked sodium hyaluronate. In addition, polyvinyl alcohol has excellent film-forming properties and adhesion, which can help improve the interfacial bonding force between the cross-linked sodium hyaluronate and the gangue ceramsite, and will not fall off during processing. Polyvinyl alcohol also has a high mechanical strength, and after being compounded with the gangue ceramsite, it can cooperate with the gangue skeleton, improve the mechanical strength of the lightweight aggregate itself, and increase the durability and strength of the concrete material.

[0021] Preferably, the gangue ceramsite composite cross-linked sodium hyaluronate and polyvinyl alcohol are prepared according to the following method:

[0022] Pretreatment of coal gangue ceramsite: adding coal gangue ceramsite to a strong acid aqueous solution, soaking for 4 to 5 hours, washing, filtering and drying to obtain pretreated coal gangue ceramsite;

[0023] Compounding of gangue ceramsite: adding sodium hyaluronate to an aqueous solution, stirring and dissolving at 40-50°C, adding a cross-linking agent, adjusting the pH value of the solution to 7-7.5, stirring and mixing at room temperature for 30-60 minutes, adding a polyvinyl alcohol aqueous solution with a mass fraction of 10-15%, and mixing to obtain a reaction solution; adding pretreated gangue ceramsite to the reaction solution, stirring and dispersing at 30-40°C for 5-6 hours, and finally washing and drying to obtain gangue ceramsite compounded with cross-linked sodium hyaluronate and polyvinyl alcohol.

[0024] Preferably, the strong acid aqueous solution includes a combination of one or more of a hydrochloric acid aqueous solution, a nitric acid aqueous solution and a sulfuric acid aqueous solution with a mass fraction of 10 to 20%.

[0025] Preferably, the preparation method of coal gangue ceramsite composite cross-linked sodium hyaluronate is as follows:

[0026] Sodium hyaluronate is added to an aqueous solution, stirred and dissolved at 40-50° C., a cross-linking agent is added, the pH value of the solution is adjusted to 7-7.5, and the mixture is stirred and mixed at room temperature for 30-60 minutes to obtain a reaction solution; pretreated gangue ceramsite is added to the reaction solution, stirred and dispersed at 30-40° C. for 5-6 hours, and finally washed and dried to obtain gangue ceramsite composited with cross-linked sodium hyaluronate.

[0027] By adopting the above technical solution, the gangue ceramsite is first pretreated, and after acidification, the gangue ceramsite can expose more active groups, which can enhance the binding force with the cross-linked sodium hyaluronate and polyvinyl alcohol. Further, the sodium hyaluronate and the cross-linking agent are pre-reacted, and the polyvinyl alcohol aqueous solution is added and mixed with each other, and the molecular chains of the two are entangled, and then compounded to the surface of the gangue ceramsite, so as to improve the water release ability and mechanical properties of the ceramsite.

[0028] Furthermore, the concrete lightweight aggregate composed of gangue ceramsite and gangue ceramsite sand obtained by the above technical solution can adapt to concrete materials of different strength grades, and can support concrete materials with a maximum strength of LC120, and also has excellent water release capacity and mechanical properties in high-strength concrete. At the same time, it can also greatly reduce the dead weight of concrete. Compared with ordinary concrete, the dead weight of the obtained lightweight concrete can be reduced by 20% to 30%, which can meet the current development requirements for lightweight concrete.

[0029] In a second aspect, the present invention provides a method for preparing a self-curing lightweight concrete made of coal gangue lightweight aggregate, comprising the following process steps:

[0030] S1. Pre-wetting the gangue ceramsite;

[0031] S2. The pre-wetted gangue ceramsite, mineral powder, fly ash, gangue sand and cement are stirred and mixed to obtain a premix;

[0032] S3. Add water reducing agent and water to the premix, and stir evenly to obtain gangue lightweight aggregate self-curing lightweight concrete.

[0033] By adopting the above technical scheme, in the preparation process of lightweight concrete, the gangue ceramsite is first pre-wetted, and part of the moisture has been absorbed and stored by the gangue ceramsite and the cross-linked sodium hyaluronate and polyvinyl alcohol compounded on the ceramsite, which can improve the dispersion and compatibility of the gangue ceramsite in the cementitious material, improve the interfacial bonding strength between the two, and can also more advantageously play a self-curing role, greatly reducing the probability of shrinkage deformation of lightweight concrete.

[0034] Beneficial effects of the present invention:

[0035] 1. The present invention selects coal gangue ceramsite and coal gangue sand as lightweight aggregates for concrete, which can greatly reduce the weight of concrete. The loose and porous structure of coal gangue ceramsite has certain water absorption and water storage capacity, and can release water to the outside when the humidity inside the concrete decreases, thereby promoting the hydration process of cement and achieving the effect of self-curing.

[0036] 2. The gangue ceramsite used in the present invention is compounded with cross-linked sodium hyaluronate, which has a large number of hydrophilic groups and a three-dimensional cross-linked network structure, which can better store liquid water in the network structure of the polymer, improve the ability of the gangue ceramsite to release water, and can also enhance the bonding force between the gangue ceramsite and the cementitious material, forming a more solid structure and improving the strength of lightweight concrete. In addition, in order to solve the problem that the strength of the cross-linked sodium hyaluronate decreases significantly after absorbing a large amount of water and the compatibility with the gangue ceramsite is poor, the gangue ceramsite is also compounded with polyvinyl alcohol, which can enhance the interfacial bonding force between the two, improve the water retention capacity, and enhance the mechanical strength of the gangue ceramsite itself. DETAILED DESCRIPTION

[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Preparation Example

[0039] Preparation Example 1: A composite cross-linked sodium hyaluronate coal gangue ceramsite is prepared according to the following method:

[0040] Pretreatment of coal gangue ceramsite: 10 g of cylindrical coal gangue ceramsite (average particle size of 14 mm) was added to a 15% nitric acid aqueous solution, and after immersion for 5 h, the pretreated coal gangue ceramsite was obtained by washing, filtering and drying;

[0041] Compounding of coal gangue ceramsite: 1g sodium hyaluronate (molecular weight 0.8×10 6 ~2×10 6 ) was added into 100 mL of aqueous solution, stirred and dissolved at 45 ° C, 0.8 g of glutaraldehyde was added, the pH value of the solution was adjusted to 7.5, and the mixture was stirred and mixed at room temperature for 40 min to obtain a reaction solution; 10 g of pretreated coal gangue ceramsite was added to the reaction solution, stirred and dispersed at 35 ° C for 6 h, and finally washed and dried to obtain coal gangue ceramsite composited with cross-linked sodium hyaluronate.

[0042] Preparation Example 2, a coal gangue ceramsite composite with cross-linked sodium hyaluronate, is different from Preparation Example 1 only in that the added amount of sodium hyaluronate is 0.8 g and the added amount of glutaraldehyde is 0.6 g.

[0043] Preparation Example 3, a coal gangue ceramsite composite with cross-linked sodium hyaluronate, is different from Preparation Example 1 only in that the added amount of sodium hyaluronate is 0.5 g.

[0044] Preparation Example 4, a coal gangue ceramsite composite with cross-linked sodium hyaluronate, is different from Preparation Example 1 only in that the added amount of sodium hyaluronate is 1.5 g.

[0045] Preparation Example 5, a coal gangue ceramsite composited with sodium hyaluronate, is different from Preparation Example 1 only in that, during the composite process of the coal gangue ceramsite, the following method is used:

[0046] 1 g of sodium hyaluronate (molecular weight 0.8×10 6 ~2×10 6 ) was added to 100 mL of aqueous solution, stirred and dissolved at 45 ° C, and the pH value of the solution was adjusted to 7.5 to obtain a reaction solution; 10 g of pretreated coal gangue ceramsite was added to the reaction solution, stirred and dispersed at 35 ° C for 6 h, and finally washed and dried to obtain coal gangue ceramsite composited with sodium hyaluronate.

[0047] Preparation Example 6, a composite cross-linked sodium hyaluronate and polyvinyl alcohol coal gangue ceramsite, is different from Preparation Example 1 only in that the composite process of the coal gangue ceramsite is carried out according to the following method:

[0048] 1 g of sodium hyaluronate (molecular weight 0.8×10 6 ~2×10 6 ) was added to 100 mL of aqueous solution, stirred and dissolved at 45 °C, 0.8 g of glutaraldehyde was added, the pH value of the solution was adjusted to 7.5, stirred and mixed at room temperature for 40 min, and 4 g of polyvinyl alcohol (molecular weight 5×10 4 ~8×10 4 ) aqueous solution, and mixing to obtain a reaction solution; adding 10g of pretreated gangue ceramsite to the reaction solution, stirring and dispersing at 35°C for 6h, and finally washing and drying to obtain gangue ceramsite composited with cross-linked sodium hyaluronate and polyvinyl alcohol.

[0049] Preparation Example 7, a coal gangue ceramsite composite of cross-linked sodium hyaluronate and polyvinyl alcohol, is different from Preparation Example 6 only in that the added amount of the polyvinyl alcohol aqueous solution with a mass fraction of 10% is 1 g.

[0050] Preparation Example 8, a coal gangue ceramsite composite of cross-linked sodium hyaluronate and polyvinyl alcohol, is different from Preparation Example 6 only in that the added amount of the polyvinyl alcohol aqueous solution with a mass fraction of 10% is 8g.

[0051] Example

[0052] Example 1, a self-curing lightweight concrete made of coal gangue lightweight aggregate is prepared according to the following process steps:

[0053] S1. Pre-wetting the composite cross-linked sodium hyaluronate gangue ceramsite prepared in Preparation Example 1;

[0054] S2. The pre-wetted gangue ceramsite, mineral powder (particle size of 0.075 mm to 0.15 mm), fly ash (particle size of 100 to 300 μm), gangue ceramsite (average particle size of 1 mm) and ordinary silicate PO52.5 cement are stirred and mixed to obtain a premix;

[0055] S3. Add polycarboxylate water reducer (Point-400S) and water to the premix, and stir evenly to obtain coal gangue lightweight aggregate self-curing lightweight concrete.

[0056] The raw material mass ratio of the obtained gangue light aggregate self-curing lightweight concrete is: 22% cement, 2% mineral powder, 5% fly ash, 30% gangue ceramsite, 28% gangue ceramsite, 1% water reducer and 12% water.

[0057] Embodiments 2 to 5 are self-curing lightweight concrete made of coal gangue lightweight aggregate. The difference from Embodiment 1 is that the raw material mass ratio is adjusted, as shown in Table 1:

[0058] Table 1 Raw material mass ratio table of Example 1 to Example 5

[0059] Example 1 Example 2 Example 3 Example 4 Example 5 cement / % 22 22 22 25 20 Mineral powder / % 2 0 2 5 1 Fly ash / % 5 5 10 10 5 Gangue ceramic sand / % 30 35 25 29.5 20 Coal gangue ceramsite / % 28 25 26 20 40 Water reducing agent / % 1 1 1 0.5 2 water / % 12 12 14 10 12

[0060] Example 6, a self-curing lightweight concrete made of coal gangue lightweight aggregate, differs from Example 1 only in that an equal amount of coal gangue ceramsite with composite cross-linked sodium hyaluronate prepared in Preparation Example 2 is used to replace the coal gangue ceramsite with composite cross-linked sodium hyaluronate prepared in Preparation Example 1.

[0061] Example 7, a self-curing lightweight concrete made of coal gangue lightweight aggregate, differs from Example 1 only in that an equal amount of coal gangue ceramsite with composite cross-linked sodium hyaluronate prepared in Preparation Example 3 is used to replace the coal gangue ceramsite with composite cross-linked sodium hyaluronate prepared in Preparation Example 1.

[0062] Example 8, a self-curing lightweight concrete made of coal gangue lightweight aggregate, differs from Example 1 only in that an equal amount of coal gangue ceramsite with composite cross-linked sodium hyaluronate prepared in Preparation Example 4 is used to replace the coal gangue ceramsite with composite cross-linked sodium hyaluronate prepared in Preparation Example 1.

[0063] Example 9, a self-curing lightweight concrete made of coal gangue lightweight aggregate, differs from Example 1 only in that the coal gangue ceramsite containing composite cross-linked sodium hyaluronate prepared in Preparation Example 1 is replaced with an equal amount of coal gangue ceramsite containing composite cross-linked sodium hyaluronate and polyvinyl alcohol prepared in Preparation Example 6.

[0064] Example 10, a self-curing lightweight concrete made of coal gangue lightweight aggregate, differs from Example 1 only in that the coal gangue ceramsite containing composite cross-linked sodium hyaluronate prepared in Preparation Example 1 is replaced with an equal amount of coal gangue ceramsite containing composite cross-linked sodium hyaluronate and polyvinyl alcohol prepared in Preparation Example 7.

[0065] Example 11, a self-curing lightweight concrete made of coal gangue lightweight aggregate, differs from Example 1 only in that the coal gangue expanded clay containing composite cross-linked sodium hyaluronate prepared in Preparation Example 1 is replaced by an equal amount of coal gangue expanded clay containing composite cross-linked sodium hyaluronate and polyvinyl alcohol prepared in Preparation Example 8.

[0066] Comparative Example

[0067] Comparative Example 1, a self-curing lightweight concrete made of coal gangue lightweight aggregate, is different from Example 1 only in that the composite cross-linked sodium hyaluronate coal gangue ceramsite prepared in Preparation Example 1 is replaced by an equal amount of composite sodium hyaluronate coal gangue ceramsite prepared in Preparation Example 5.

[0068] Comparative Example 2, a self-curing lightweight concrete made of coal gangue lightweight aggregate, is different from Example 1 only in that the coal gangue ceramsite of the composite cross-linked sodium hyaluronate prepared in Preparation Example 1 is replaced with an equal amount of untreated coal gangue ceramsite.

[0069] Comparative Example 3 is a self-curing lightweight concrete made of coal gangue lightweight aggregate. The only difference from Example 1 is that the coal gangue ceramic sand is replaced by an equal amount of fine sand (fineness modulus is 2.6).

[0070] Comparative Example 4, a self-curing lightweight concrete made of coal gangue lightweight aggregate, is different from Example 1 only in that an equal amount of crushed stone (average particle size of 14 mm) is used to replace the coal gangue ceramsite of the composite cross-linked sodium hyaluronate prepared in Preparation Example 1.

[0071] Comparative Example 5, a self-curing lightweight concrete made of coal gangue lightweight aggregate, differs from Example 1 only in that the coal gangue ceramsite is replaced by an equal amount of fine sand (fineness modulus is 2.6); and the coal gangue ceramsite of the composite cross-linked sodium hyaluronate prepared in Preparation Example 1 is replaced by an equal amount of crushed stone (average particle size is 3 mm).

[0072] Performance testing

[0073] Sample preparation: The concrete obtained in the examples and comparative examples was molded and placed outdoors for natural curing for 28 days before testing various properties.

[0074] Performance Test:

[0075] (1) Compressive strength test: According to the relevant records in GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", the 28d compressive strength of concrete was tested.

[0076] (2) Shrinkage test: According to the relevant records in GB / T 50082-2009 "Standard for test methods for long-term performance and durability of ordinary concrete", the shrinkage rate of concrete at 28 days was tested.

[0077] (3) Weight density test: Test the weight density of concrete after 28 days of curing.

[0078] The above test results are shown in Table 2:

[0079] Table 2 Performance test results

[0080]

[0081] According to Table 2, in combination with Example 1 and Example 2 to Example 6, it can be seen that the various properties of Example 2 to Example 6 are not much changed compared with Example 1. The reason is that compared with Example 1, Example 2 to Example 6 only adjust the raw materials and the raw material ratio within the required range, which has little effect on the final concrete performance.

[0082] Combining Example 1, Example 7, Example 8 and Comparative Example 2, it can be seen that the compressive strength of Example 7, Example 8 and Comparative Example 2 is reduced compared with Example 1, and the shrinkage rate of Comparative Example 2 is significantly increased compared with Example 1. The reason is that in Example 7, the amount of cross-linked sodium hyaluronate compounded with gangue ceramsite is reduced, and the water release capacity is slightly reduced. The bonding force between the gangue ceramsite and the cementitious material is also reduced, resulting in a decrease in compressive strength; in Comparative Example 2, the gangue ceramsite is not composited with cross-linked sodium hyaluronate, so the performance is significantly reduced. In Comparative Example 8, the amount of cross-linked sodium hyaluronate compounded with gangue ceramsite is increased. Excessive cross-linked sodium hyaluronate will affect the loose and porous structural characteristics of the gangue ceramsite itself, blocking some of the cavities, which will affect the firm bonding of the cementitious material and the gangue ceramsite.

[0083] Combining Example 1 and Examples 9 to 11, it can be seen that the performance of Examples 9 to 11 is slightly enhanced compared to that of Example 1. The reason is that the gangue ceramsite in Example 9 is also compounded with polyvinyl alcohol, which can improve the water retention performance of the material while increasing the strength of the gangue ceramsite itself, thereby improving the overall performance.

[0084] Combining Example 1 and Comparative Example 1, it can be seen that the compressive strength of Comparative Example 1 decreases and the shrinkage rate increases compared with Example 1. The reason is that the sodium hyaluronate composited with coal gangue ceramsite in Comparative Example 1 is not a cross-linked structure, which will greatly affect the ability of sodium hyaluronate to store water, and the self-curing ability of concrete is reduced, resulting in a decrease in strength and signs of shrinkage and deformation.

[0085] In combination with Example 1 and Comparative Examples 3 to 5, it can be seen that the strength of Comparative Examples 3 to 5 is slightly increased compared with Example 1, but the shrinkage rate is significantly increased, and the weight density is also significantly increased, indicating that the addition of coal gangue expanded clay and coal gangue sand can significantly reduce the weight density of concrete, and can achieve the goal of lightweight concrete. The concrete after lightweight treatment of coal gangue still has excellent compressive strength. At the same time, its self-curing ability also makes the obtained lightweight concrete have self-curing ability, which effectively avoids the shrinkage and deformation problems that may be caused by lightweighting.

[0086] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0087] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A self-curing lightweight concrete made of coal gangue light aggregate, characterized in that: The invention comprises the following raw materials in mass fractions: 20% to 25% cement, 0% to 5% mineral powder, 5% to 10% fly ash, 25% to 40% coal gangue ceramsite, 20% to 40% coal gangue ceramsite, 0.5% to 2% water reducing agent and 10% to 20% water; the coal gangue ceramsite is compounded with cross-linked sodium hyaluronate.

2. The self-curing lightweight concrete made of coal gangue lightweight aggregate according to claim 1, characterized in that: The gangue ceramsite is cylindrical gangue ceramsite; the particle size of the gangue ceramsite is 12 mm to 14 mm.

3. The self-curing lightweight concrete made of coal gangue lightweight aggregate according to claim 1, characterized in that: The raw materials of the gangue ceramsite composite cross-linked sodium hyaluronate include gangue ceramsite, sodium hyaluronate and a cross-linking agent in a mass ratio of 1: (0.08-1): (0.06-0.08).

4. The self-curing lightweight concrete made of coal gangue lightweight aggregate according to claim 3, characterized in that: The cross-linking agent includes one or more of 1,4-butanediol diglycidyl ether, glutaraldehyde, polyethylene glycol diglycidyl ether and carbodiimide.

5. The self-curing lightweight concrete made of coal gangue lightweight aggregate according to claim 1, characterized in that: The coal gangue ceramsite is also compounded with polyvinyl alcohol.

6. The self-curing lightweight concrete made of coal gangue lightweight aggregate according to claim 5, characterized in that: The mass ratio of the coal gangue ceramsite to the polyvinyl alcohol is 1:(0.03-0.05).

7. The self-curing lightweight concrete made of coal gangue lightweight aggregate according to claim 5, characterized in that: The gangue ceramsite composite cross-linked sodium hyaluronate and polyvinyl alcohol are prepared according to the following method: Pretreatment of coal gangue ceramsite: adding coal gangue ceramsite to a strong acid aqueous solution, soaking for 4 to 5 hours, washing, filtering and drying to obtain pretreated coal gangue ceramsite; Compounding of gangue ceramsite: adding sodium hyaluronate to an aqueous solution, stirring and dissolving at 40-50°C, adding a cross-linking agent, adjusting the pH value of the solution to 7-7.5, stirring and mixing at room temperature for 30-60 minutes, adding a polyvinyl alcohol aqueous solution with a mass fraction of 10-15%, and mixing to obtain a reaction solution; adding pretreated gangue ceramsite to the reaction solution, stirring and dispersing at 30-40°C for 5-6 hours, and finally washing and drying to obtain gangue ceramsite compounded with cross-linked sodium hyaluronate and polyvinyl alcohol.

8. The gangue light aggregate self-curing lightweight concrete according to claim 1, characterized in that: The particle size of the coal gangue ceramic sand is 0.2 mm to 1.5 mm.

9. A method for preparing a self-curing lightweight concrete made of coal gangue lightweight aggregate according to any one of claims 1 to 8, characterized in that: The process steps include: S1. Pre-wetting the gangue ceramsite; S2. The pre-wetted gangue ceramsite, mineral powder, fly ash, gangue sand and cement are stirred and mixed to obtain a premix; S3. Add water reducing agent and water to the premix, and stir evenly to obtain gangue lightweight aggregate self-curing lightweight concrete.

Citation Information

Patent Citations

  • Process for preparing cross-linked sodium hyaluronate microspheres capable of being adopted as emboliaztion agent by adopting sodium hyaluronate as raw material

    CN103333351A

  • Light-weight aggregate concrete capable of effectively utilizing coal gangue slag

    CN105948597A

  • Functional concrete additive based on organic-inorganic carrier and preparation method thereof

    CN108264258A

  • Preparation method of concrete having no strength negative effect and high internal curing efficiency

    CN108751811A

  • Set retarding reinforcing agent for permeable concrete and method for preparing set retarding reinforcing agent

    CN109485295A